Community Empowerment to Improve Sustainable Agricultural Productivity through Smart Farming Based on Floating Solar Power Plants in Kesongo Village, Semarang Regency - Herlambang, Yusuf Dewantoro; Mujahidin, Irfan; Marliyati; Ningtias, Dieta Wahyu Asry; Ningrum, Siti Mardiyanti; Widhaninggar, Diana Fika; Bayu, Tatar; Prasetya, Valendry Naufal (International Journal of Research in Vocational Studies (IJRVOCAS), 2025)
The global energy crisis and increasing demand for agricultural irrigation have driven the need for more efficient and environmentally friendly renewable energy sources. This study aims to design and implement an Internet of Things (IoT)-based Solar Water Pumping System (SWPS) to support smart irrigation in rural areas. The system was designed in Kesongo Village, Tuntang District, Semarang Regency, utilizing a 20 kWp floating solar power plant (PLTS) as the main energy source to operate a 2.2 kW water pump. IoT technology integration was carried out through an ESP32 microcontroller, pressure sensors, and relay modules that enable real-time monitoring and control of the pump via mobile devices. System testing was conducted with valve openings varying from 25% to 100% to evaluate the hydraulic performance and efficiency of the pump. Test results showed the highest efficiency of 46.95% at a head of 13.28 m with the valve fully open, while the lowest efficiency of 28.10% was obtained at a head of 14.88 m with a valve opening of 25%. The system proved capable of irrigating an area of 131,157.36 m² with a stable water supply. This study confirms that IoT-based PATS has great potential in optimizing water distribution, reducing fossil fuel use, and supporting sustainable agricultural resource management. Thus, this study provides an innovative alternative solution to increase agricultural productivity.